Divertor plasma behaviors with neon seeding at different locations on EAST with ITER-like divertor. (1st August 2022) - Meng, L.Y.; Wang, L.; Wang, H.Q.; Deng, G.Z.; Si, H.; Li, K.D.; Xu, G.S.; Yuan, Q.P.; Guo, H.Y.; Eldon, D.; Garofalo, A.M.; Leonard, A.W.; et al.
Abstract: For the problem of excessively high divertor heat flux, active impurity seeding is an effective method to radiate the plasma energy reaching the divertor and thus achieve the divertor detachment. Neon is a very effective radiation impurity on many current tokamaks, which is also a candidate species to be applied on ITER. In the EAST 2019 experimental campaign, a series of experiments were performed by seeding a mixture of neon and deuterium (Ne-D2 ) for detachment and core-edge-divertor integration in H-mode plasmas. The divertor partial detachment with high-confinement core plasma has been achieved by using Ne-D2 seeding in EAST with ITER-like tungsten divertor. Both the plasma stored energy and H 98, y 2 > 1.1 are maintained, with the divertor electron temperature, heat flux and the surface temperature near the strike point being all significantly reduced. The differences between Ne-D2 seeding at the scrape-off layer (SOL) upstream and downstream have been experimentally investigated in detail. It is found that impurity seeding at SOL downstream is more beneficial to reducing the divertor electron temperature and peak heat flux. By comparison with experiments using divertor D2 fueling, it is further demonstrated that gas seeding in the SOL downstream will enrich more particles near the strike point, while the seeding in the SOL upstream will influence the entire outer target more evenly. Furthermore, in most of the experiments, gas seeding does not cause obvious toroidal asymmetry in the divertor plasma. However, when D2 is injected in an amount similar to that used to build the plasma, it causes the particle flux near the gas-puff to increase locally, i.e., much more than that at the toroidal location far from the gas-puff location. It is a competition between particle source and transport. When the particle source is stronger, it will naturally increase the local particles. In addition, dedicated experiments with different poloidal distances between impurity seeding and strike point on the radiation ability were carried out. Both experimental results and SOLPS simulation show that the seeding close to the strike point is more conducive to neon ionization and energy radiation.